Juliet 1.1 C/C++ and Java Test Suite. - Boland, Tim; Black, Paul E. (Computer (00189162), 2012)
Juliet Test Suite 1.1 offers test cases for assessing the effectiveness of static analyzers and other software-assurance tools.